Minimally Invasive Surgical Access to Aortic Valve Replacement: Comparison Between Minithoracotomy & Ministernotomy in A Systematic Review - Micali, Linda Renata; Abualsaud, Mohammed; Parise, Gianmarco; Tetta, Cecilia; Parise, Orlando; Matteucci, Francesco; Jong, Monique de; Bonacchi, Massimo; Gelsomino, Sandro (Cardiology and Cardiovascular Medicine, 2019)
Background: Minimally invasive aortic valve replacement (MIAVR) procedures are starting to be accepted as the standard procedures for aortic valve diseases. However, only a limited number of studies have directly compared mini-thoracotomy (MT) to mini-sternotomy (MS). Therefore, the aim of this review was to summarize the available literature for comparison between the procedures to have a better understanding of the risks and benefits to guide future procedures. Methods: A literature search for MT and MS was carried out using two literature databases. Relevant articles were identified and assessed through the inclusion and exclusion criteria. Results: 15 studies were identified for inclusion in this review. Comparable results were identified between MT and MS in terms of 30-day mortality. In addition, there was no difference in the incidence of stroke, reoperation for bleeding, and wound infection. In contrast, MT showed longer cardiopulmonary bypass (CPB) and cross-clamping durations than MS. Conclusion: Both MT and MS surgical approaches are reliable, efficient, and comparable. These findings have to be confirmed by large randomized trials